2018
DOI: 10.3390/ma11081359
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Dumbbell-Like β-Bi2O3/Graphene Nanocomposites and Their Highly Efficient Photocatalytic Activity

Abstract: β-Bi2O3 decorated graphene nanosheets (β-Bi2O3/GN) were prepared by a facile solution mixing method. The crystal structure, surface morphology, and photo absorbance properties of the products were characterized by XRD, SEM, and UV-VIS diffuse reflection, respectively. Moreover, the effect of graphene content on photocatalytic activity was systematically investigated, and the results indicated that these composites possessed a high degradation rate of Rhodamine B (RhB), which was three times higher than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 26 publications
7
13
0
Order By: Relevance
“…The Figure 1 shows the crystal plane (201) and (220) at 2θ were around 27.9 • and 32.6 • , which correspond to the tetragonal β-Bi 2 O 3 for the annealed sample at 550 • C. This is matched to the data in the JCPDS card No. 00-27-0050 and previous research [36]. Our Bi 5 O 7 I pattern is in line with the reported research [37].…”
Section: Raman Spectroscopysupporting
confidence: 93%
See 2 more Smart Citations
“…The Figure 1 shows the crystal plane (201) and (220) at 2θ were around 27.9 • and 32.6 • , which correspond to the tetragonal β-Bi 2 O 3 for the annealed sample at 550 • C. This is matched to the data in the JCPDS card No. 00-27-0050 and previous research [36]. Our Bi 5 O 7 I pattern is in line with the reported research [37].…”
Section: Raman Spectroscopysupporting
confidence: 93%
“…Apart from Bi 5 O 7 I, the annealed sample at a higher temperature (550 • C) resulted in the biggest bismuth-based material like a dumbbell, with a thickness around 75 nm. The same morphology of this dumbbell-like material was also confirmed in the previous report for β-Bi 2 O 3 [36]. Worm-like structures which are similar to our β-Bi 2 O 3 morphology were also reported [31].…”
Section: Optical Studysupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, it is easy to notice the appearance of new vibration peaks after the Bi deposition. In the literature, many authors have reported that metal-oxygen vibrations modes occur in the range of the spectrum from 400 to 700 cm −1 [ 28 , 29 , 30 ], while other works have reported that these latter vibrations appear below 1000 cm −1 [ 31 , 32 ]. Hence, the new peaks situated at 614, 733, and 940 cm −1 can be attributed to the formation of new bismuth–oxygen bands.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the new peaks situated at 614, 733, and 940 cm −1 can be attributed to the formation of new bismuth–oxygen bands. The peaks at 1170 and 1460 cm −1 were assigned to the C–O–Bi and C=O vibrations, respectively [ 28 , 29 ]. The band at around 3000 cm −1 is attributed to the Bi–OH vibration [ 28 ].…”
Section: Resultsmentioning
confidence: 99%